Evolving China's energy policy : origins and implications. - Chen, Xilai. (2008)
China's energy demand has been increasing sharply together with the high economic growth. Yet the domestic output can no longer catch up with the demand. As the result, a change of China's energy policy is under way so as to protect the national security. On the one hand, China is trying to retain maximum self-sufficiency by exploiting domestic potentials. On the other hand, it is actively playing an important role in the international energy system. This paper examines the structure of the evolving China's energy policy, highlights the origins of the shift, and analyzes its implications particularly to the Sino-American relationship.